Synergistic effects of Aurora A and AKT inhibitors combined with radiation in colon cancer cells - Qiuxia Peng; Wei Zhou; Jie Li; Danqing Liu (Discover Oncology)
Abstract Purpose This study aimed to investigate the synergistic effects of combining Aurora A and AKT inhibitors with radiation therapy on colon cancer cells and to elucidate the underlying mechanisms. Methods: Human colon cancer cell lines HCT-15 and HCT-116 were treated with Alisertib (Aurora A inhibitor), MK2206 (AKT inhibitor), and radiation alone or in combination. Cell viability, cell cycle distribution, apoptosis, and DNA damage were analyzed using MTT assays, flow cytometry, Western blotting, and immunofluorescence staining, respectively. Results: The combination of Alisertib and MK2206 with radiation significantly suppressed cell proliferation, induced pronounced G2/M phase arrest, and enhanced apoptosis compared to single-agent treatments. Western blot and immunofluorescence analyses revealed elevated γ-H2AX levels, indicating increased DNA double-strand breaks. Conclusion: The integration of Aurora A and AKT inhibitors with radiation therapy synergistically enhances anticancer effects by amplifying DNA damage, disrupting mitotic progression, and inducing apoptosis. This combination represents a promising strategy for overcoming treatment resistance in colon cancer.